CSG Tree : evaluation on performance between solid modelers - Romli, Awanis; Haron, Habibollah; Mohamad Jaya, Abdul Syukor (2007)
Solid modeling theory and technology are maturing rapidly. We have seen explOsive growth in the field's sCientific literature. and many solid modelers are commercially available. Commonly a part is represented in the forms of constructive solid geometry (CSG) or Boundary Representations (B-rep). Since it is hard to use the B-rep approach to represent a variable parI, the CSG tree approach is widely applied in parametric modeling where features or geometric primitives are its basic building blocks. Many vendors are now offering intuitive 3D browsers that support the review and annotation of 3D models of complex assemblies of solids. These browsers support communication in product data management activities. help illustrate maintenance manuals, or provide interactive virtual-reality experiences for marketing, styling, or ergonomic analysis. In this paper, Constructive Solid Geometry (CSG) is a method used for representing solid objects in many contemporary solid modeling systems. The best CSG tree structure will be presented for representing the performance of the solid model. The complexity of the solid model will be presented by using solid modeler; Au/oCAD 2004 and SolidWurks 2001 plus.